2000
DOI: 10.1063/1.1315328
|View full text |Cite
|
Sign up to set email alerts
|

Lateral gettering of iron by cavities induced by helium implantation in silicon

Abstract: Lateral gettering has been studied by introducing cavities in the periphery of large active devices. Cavities were induced by helium implantation followed by a thermal treatment on samples previously contaminated by iron. Those cavities are known to be efficient to trap metallic impurities in silicon by chemisorption. The iron distribution in samples of 6×6 mm2 area has been monitored by measuring current versus voltage characteristics and interstitial iron concentrations by deep level transient spectroscopy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…88,132 Interestingly, it has been experimentally confirmed that metallic impurity atoms sre efficiently trapped near nanocavities in a silicon host matrix. 117,[133][134][135][136][137][138] Moreover, artificial cells with nanocavities can sequester poisonous heavy elements such as heavy metal atoms in the human body. 96 The void volume and inner skin associated with such nanocavities are the preferred trapping centers for impurities.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…88,132 Interestingly, it has been experimentally confirmed that metallic impurity atoms sre efficiently trapped near nanocavities in a silicon host matrix. 117,[133][134][135][136][137][138] Moreover, artificial cells with nanocavities can sequester poisonous heavy elements such as heavy metal atoms in the human body. 96 The void volume and inner skin associated with such nanocavities are the preferred trapping centers for impurities.…”
Section: Observationsmentioning
confidence: 99%
“…In other words, the nanocavities in host crystals act as a sink, and atoms spontaneously flow into nanocavities during annealing, as is shown by experiments. 122,[135][136][137][138] On the other hand, diffusion in nanostructures with negative curvature may be important in technological applications such as chemical catalysis. Recently, an interesting experiment addressing the striking enhancement of the catalytic activity for the conversion of CO and H 2 to ethanol by Rh particles confined inside nanotubes was described, and the functions of the densified charge and the very different atomic energy states in the outer and inner surface were accounted for.…”
Section: Diffusion Kinetics Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 High-energy ͑MeV͒ implantation can produce cavities deep into silicon ͑Ͼ3 m͒, in a well-defined region beyond the active region of electronic devices. Lateral gettering, which has been recently found to be efficient in the case of iron, 8 can also be used in the periphery of active devices. In the MeV energy range, however, very few investigations have been performed to study their formation and evolution upon annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent research showed that these voids have clean inner surfaces (dangling bonds) that can trap metallic impurities (Follstaedt et al, 1996). To control these unwanted impurities, gettering treatment is required, and cavities have been shown to be a powerful technique to locally getter metallic impurities (Roqueta et al, 2000). The defects induced by cavity formation can be used for very effective strain relaxation in pseudomorphic SiGe/Si heterostructures (Trinkaus et al, 2000).…”
Section: Introductionmentioning
confidence: 99%